WORKFORCE TREND AND EXISTENCE OF NEW ECONOMIC CONCEPT “NEGATIVE EMPLOYMENT” IN CONFLICT ZONE OF KASHMIR IN INDIA - Dr. Bilal Ahmad Khan (Research Parks Publishers, 2020)
Kashmir being a conflict ridden zone has far less opportunities for employment than rest of the other states. With an underdeveloped industrial sector and the inability of government to create enough jobs, there seems to be no immediate solution. The instability and lack of any conclusive resolution have left the population of Kashmir divided and uncertain about their future resulted impoverishment through the channels of reduction of the capital, income and employment, physical destruction and mass displacement of human resources. The brunt of violence resulted negligible investments with business marred by uncertainties. Serious unemployment and economic downturn during 90s, a large number of unemployed youth extremely poor sections of society joined anti-nation movement and also forced migration of Kashmiri Hindu and pundits took place. Researcher can’t look economic growth in isolation. There must be social, political and cultural harmony. Kashmir UT is the highest militarized zone in the world and this kind of military presence is highest in the world per square foot. There is no part of the world which has this kind of concentration of military presence. In the light of research work, the main objective is to look the workforce trend and examine on the existence of negative unemployment in the conflict zone Kashmir.